Teaching literacy and decreased risk of learning disabilities. - González-Valenzuela, María José; Martín-Ruiz, Isaías; Delgado-Ríos, Myriam (Universidad del Pais Vasco (UPV), 2012)
This paper’s objective is to analyze the effects of an early intervention program to reduce the numbers of subjects at risk of learning disabilities (LD) at a young age and to increase their academic achievement (AA). The general sample initially consists of 117 five year old students. They come from middle sociocultural backgrounds and have no physical, psychological or sensory handicaps. A longitudinal design has been repeatedly used with four evaluation phases and three intervention phases, two variables (percentages of subjects at risk of LD and AA) and two sample groups (IG, NIG). Results indicate that, after three years, the percentage of subjects presenting LD in the group receiving instruction (IG) is lower than those in the group not receiving instruction (NIG). The subjects from the IG also received better scores in AA than those in the NIG. These results show the long term effectiveness of systematic and planned intervention of oral and written language at a young age as a method for avoiding LD.
https://ojs.ehu.eus/index.php/psicodidactica/about
Keywords: Atención temprana; Rendimiento académico; Aprendizaje - Trastornos; Early intervention; Learning disabilities; Academic achievement